Fatores explicativos da adesão às práticas de governança de entidades fechadas de previdência complementar brasileiras - Teixeira, Bruno de Medeiros (Universidade do Vale do Rio dos Sinos, 2015)
This study aimed to analyze the factors which explain the adherence to governance practices in private supplementary pension entities (EFPC) in Brazil. In this context, this thesis was based on agency theory, which assumes the existence of information asymmetry, conflict of interest and distinct willingness to take risk in relations involving agent and principal. One of the instruments used in response to agency problems, is governance. In addition to this theoretical basis, we employed national and international empirical studies on governance in EFPC. Besides, we analyzed the Brazilian legislation for EFPC governance and the governance manual of National Superintendence of Supplementary Pension (PREVIC), the body that oversees and supervises these organizations. Considering this information, it was built set of 34 indicators of governance for EFPC, which allowed measuring the level of adherence to governance practices of these organizations. Supported by theoretical and empirical literature review on the topic, it was established a set of explanatory hypotheses of accession to the governance practices in EFPC. The variables constructed to test these hypotheses were submitted to statistical technique of multiple linear regression. The sample consists of 110 EFPC belonging to groups A, B and C of the classification established by PREVIC. The evidence used to measure the level of adherence to governance practices EFPC were collected on their web pages available on the Internet, and refer to the year 2014. For the explanatory variables, the data used refer to the year 2013, corresponding to the last period in which the accounting and financial statements were closed during data collection. The model results indicated that the EFPC that has greater assets, higher volume of invested resources, fewer participants, lower expenses on outsourcing and public sponsorship, have better level of adherence to governance practices. This study may contribute to participants, beneficiaries and other stakeholders so that they can understand the characteristics that EFPC with better governance have. It may also help to improve the governance mechanisms by the EFPC and greater use of these.
Keywords: Governança; Entidades fechadas de previdência complementar; Fatores explicativos; Governance; Private supplementary pension entities; Explanatory factors; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis